Pelatihan Digital Marketing dan Cek Kesehatan untuk Mewujudkan Masyarakat Sehat dan Sejahtera di Desa Triwidadi, Pajangan, Bantul - Hidayatullah Hidayatullah; Mursyid Mursyid; Wilis Fahlefi; Wahyudiyono Wahyudiyono; Mochamad Rofik (Universitas 45 Surabaya, 2024)
Abstract The background to this community service activity is the low understanding and skills of the people of Triwidadi Village, Pajangan, Bantul in utilizing digital technology for product marketing and the lack of access to adequate health services. The majority of people in this area are micro, small and medium enterprises (MSMEs) who have not yet optimally utilized digital technology to develop their businesses. Apart from that, access to basic health services such as routine health checks is still limited, which has an impact on people's quality of life. The formulation of the problem raised in this research is: (1) How to increase people's understanding and skills in digital marketing to increase the competitiveness of MSMEs in Triwidadi Village? (2) How to provide health check services that are easily accessible to the local community? The aim of this community service is to: (1) Increase community knowledge and skills about digital marketing through structured counseling and training activities; (2) Providing routine health check services to increase awareness and preventive action on health in the Triwidadi Village community. The results of this service activity show a significant increase in the community's understanding and skills regarding digital marketing. This is proven by the increase in the number of MSMEs that are starting to utilize digital platforms to market their products. Apart from that, the health check service provided during the activity has been well utilized by the community, as can be seen from the quite high number of participants and the results of the health check which helps the community to care more about their health condition. This activity also has a positive impact on improving people's quality of life through better access to information and health services.